2000
DOI: 10.1093/nar/28.22.4552
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the sensitivity and specificity of oligonucleotide (50mer) microarrays

Abstract: To examine the utility and performance of 50mer oligonucleotide (oligonucleotide probe) microarrays, gene-specific oligonucleotide probes were spotted along with PCR probes onto glass microarrays and the performance of each probe type was evaluated. The specificity of oligonucleotide probes was studied using target RNAs that shared various degrees of sequence similarity. Sensitivity was defined as the ability to detect a 3-fold change in mRNA. No significant difference in sensitivity between oligonucleotide pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
382
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 546 publications
(402 citation statements)
references
References 10 publications
11
382
1
3
Order By: Relevance
“…26 During preparation of the library, polymerase chain reaction is used to amplify target regions; however, high GC content reduces the efficiency of such amplification. 27 Moreover, the hybridization of capture probes to the target sequences can be hindered by high or low GC content 28 (Supplementary Table S4 online). In our study, we confirmed that both sequencing depth and coverage were dependent on GC content (Supplementary Figure S2 online).…”
Section: Discussionmentioning
confidence: 99%
“…26 During preparation of the library, polymerase chain reaction is used to amplify target regions; however, high GC content reduces the efficiency of such amplification. 27 Moreover, the hybridization of capture probes to the target sequences can be hindered by high or low GC content 28 (Supplementary Table S4 online). In our study, we confirmed that both sequencing depth and coverage were dependent on GC content (Supplementary Figure S2 online).…”
Section: Discussionmentioning
confidence: 99%
“…RNA-Seq overcomes several shortcomings of microarray-based detection of transcripts, including probe cross-hybridization (9), restricted signal dynamic range, and low sensitivity and specificity, which often lead to difficulties in the detection of low abundance transcripts and discrimination between similar sequences. Sequence level transcript information has much greater power to distinguish between paralogous genes, better detection of low abundance transcripts, and allows replicable digital quantification based upon counting sequence reads (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…DNA microarrays are technology to profile the expression of thousands of transcripts simultaneously (Brown and Botstein, 1999;Lockhart and Winzeler, 2000;Noordewier and Warren, 2001), and two different types of microarray technologies are available; Genechips (Affymetrix platform) and spotted microarrays. The Genechips produced by photolithography and hybridize the single cRNA probe have certain advantages over spotted microarray, such as that crosshybridization could be avoided, quality control by sequence validation of PCR clones is not required, and noncompetitive nature of hybridization make small amount of RNA sample detectable (Kane et al, 2000;Lockhart and Winzeler, 2000). As this platform is not accessible for every laboratory, spotted microarrays of longer oligonucleotides (50-70 mer) are becoming attractive and alternative platform (Hughes et al, 2001).…”
Section: Introductionmentioning
confidence: 99%